NURSING STUDENT'S PERCEPTION OF WORK-BASED LEARNING PROGRAMS: SYSTEMATIC REVIEW - Hindriati, Titik; Asrial, Asrial; Rusdi, Muhammad; Herlambang, Herlambang (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Work-based learning (WBL) is a critical approach in nursing education that emphasizes experiential learning. However, qualitative studies frequently report challenges nursing students face in WBL settings. This study aims to systematically analyze qualitative evidence on nursing students’ experiences in work-based learning within healthcare organizations, highlighting key challenges and areas for improvement. A systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines. Literature searches were performed using Medline, Embase, CINAHL, and JSTOR databases. Quality appraisal was conducted using the JBI-QARI framework. The initial search yielded 311 studies, seven of which were deemed eligible based on inclusion criteria that focused on qualitative English-language studies involving nursing students. The review identified three major challenges in WBL: (1) time constraints limiting learning opportunities, (2) workplace environmental factors such as lack of mentorship and high-pressure conditions, and (3) unclear benefits perceived by students in WBL programs. These factors contribute to varying levels of engagement and satisfaction among nursing students. This study is the first systematic review to evaluate nursing students’ perceptions of WBL, offering a comprehensive analysis of recurring issues. The findings provide valuable insights for educational institutions and healthcare organizations to enhance WBL effectiveness through structured mentorship, improved scheduling, and targeted support strategies, ultimately bridging the gap between theoretical knowledge and practical experience in nursing education.